Medicinal plants diversity among the oromo community in heban-arsi district of Ethiopia used to manage human and livestock ailments - Nuro, Geritu; Tolossa, Ketema; Arage, Mahlet; Giday, Mirutse (Frontiers in Pharmacology, 2024)
Introduction: Medicinal plants are commonly employed mainly due their accessibility, affordability and potency. However, medicinal plants and the associated knowledge are disappearing at an alarming rate due to natural and anthropogenic causes and thus a need for their proper documentation conservation. This study was performed to document traditional knowledge related to use of medicinal plants in Heban-Arsi district, West-Arsi Zone, Oromia Regional State, Ethiopia.Methods: Interviews were conducted with 185 informants to identify medicinal plants used in traditional therapies in the study area. Informant consensus factor (ICF), rank order priority (ROP) values were computed, and preference ranking exercises were performed to assess the relative importance of medicinal plants. Descriptive and inferential statistics were used to measure and compare medicinal plants knowledge between social groups.Results: A total of 120 medicinal plants were identified for being used to treat different human and animal illnesses in the study area. Most of the medicinal plants (76.4%) were uncultivated ones obtained from different habitats. Leaf was the most frequently used plant part constituting 62.6% of preparations. Oral was the most commonly used route of remedy administration (46%) in treating diseases. Gastrointestinal ailments category had the highest ICF value (0.83). In the study area, the highest rank order priority (ROP) values were recorded for Dombeya torrida (J.F. Gmel.), Artemisia absinthium L., Balanites aegyptiaca (L.) Del., Combretum pisoniiflorum Klotzsch) Engl., Celtis africana Burm. f, Ocimum gratissimum L. and Lagenaria sp. for their uses against snake poison, tuberculosis, liver disorder, stomachache, tuberculosis, febrile illness and liver disorder, respectively, each scoring a value of 100. Significant differences in medicinal plant use knowledge were recorded between male and female informants of different educational level, age and experience. Anthropogenic factors were the primary threats to medicinal plants in the area.The study area was found to be rich in medicinal plants that are useful in treating a wide range of human and animal illnesses. In future pharmacological and phytochemical investigations, priority needs to be given to medicinal plants of the highest ROP values and those that were reported against ailment categories scoring the highest ICF values.